A Novel Stopped-Flow Assay for Quantitating Carbonic-Anhydrase Activity and Assessing Red-Blood-Cell Hemolysis - Zhao, Pan; Geyer, R. Ryan; Boron, Walter F. (Frontiers in Physiology, 2017)
We report a novel carbonic-anhydrase (CA) assay and its use for quantitating red-blood-cell (RBC) lysis during stopped-flow (SF) experiments. We combine two saline solutions, one containing HEPES/pH 7.03 and the other, 1% CO2/44 mM HCO3−/pH 8.41, to generate an out-of-equilibrium CO2/HCO3− solution containing 0.5% CO2/22 HCO3−/pH 7.25 (10C) in the SF reaction cell. CA catalyzes relaxation of extracellular pH to 7.50: HCO3− + H+  CO2 + H2O. Proof-of-concept studies (no intact RBCs) show that the pH-relaxation rate constant (kΔpH)—measured via pyranine fluorescence—rises linearly with increases in [bovine CAII] or [murine-RBC lysate]. The y-intercept (no CA) was kΔpH=0.0183 s−1. Combining increasing amounts of murine-RBC lysate with ostensibly intact RBCs (pre-SF hemolysis0.4%)—fixing total [hemoglobin] at 2.5 M in the reaction cell to simulate hemolysis from ostensibly 0% to 100%—causes kΔpH to increase linearly. This y-intercept (0% lysate/100% ostensibly intact RBCs) was kΔpH=0.0820 s−1, and the maximal kΔpH (100% lysate/0% intact RBCs) was 1.304 s−1. Thus, mean percent hemolysis in the reaction cell was 4.9%. Phenol-red absorbance assays yield indistinguishable results. The increase from 0.4% to 4.9% presumably reflects mechanical RBC disruption during rapid mixing. In all fluorescence studies, the CA blocker acetazolamide reduces kΔpH to near-uncatalyzed values, implying that all CA activity is extracellular. Our lysis assay is simple, sensitive, and precise, and will be valuable for correcting for effects of lysis in physiological SF experiments. The underlying CA assay, applied to blood plasma, tissue-culture media, and organ perfusates could assess lysis in a variety of applications.